Pengaruh Disiplin Kerja dan Quality of Work Life (QWL) terhadap Kinerja Karyawan KSP Kopdit Suru Pudi Koting Kabupaten Sikka - Matias Trivonius Reinaldo; Emanuel Wellem; Paulus Juru (Journal of Management and Creative Business, 2024)
This research aimed to (1) describe employee performance, work discipline, and quality of work life; (2) analyze the influence of work discipline and quality of work life on employee performance either partially or simultaneously. The population in this research were Suru Pudi Koting Credit Union employees, totaling 30 people. Due to limited population, this research was conducted by census or saturated sampling. Data were collected through questionnaires and analyzed using descriptive methods and inferential statistics, namely multiple linear regression. Hypothesis testing was done through the F-test and t-test. The results of the descriptive analysis showed that the variables of employee performance, work discipline, and quality of work life were in good category. The statistical results of the t-test showed that the variables of work discipline and quality of work life had a positive and significant influence on employee performance. The statistical results of the F-test showed that simultaneously the variables of work discipline and quality of work life had a siqnificant influence on employee performaance. The results of the determination analysis showed that the two independent variables in this study were able to explain the fluctuation of employee performance in Suru Pudi Koting Credit Union by 63.8%.